Targeting hypoxia in solid and haematological malignancies - Harris, Bill; Saleem, Sana; Cook, Natalie; Searle, Emma (Journal of experimental & clinical cancer research, 2022)
Tumour hypoxia is a known and extensively researched phenomenon that occurs in both solid and haematological malignancies. As cancer cells proliferate, demand for oxygen can outstrip supply reducing tumour oxygenation. In solid tumours this is contributed to by disorganized blood vessel development. Tumour hypoxia is associated with resistance to treatment, more aggressive disease behaviour and an increased likelihood of metastatic progression. It can be measured using both invasive and non-invasive methods to varying degrees of accuracy. The presence of hypoxia stimulates a complex cellular network of downstream factors including Hypoxia Inducible Factor 1 (HIF1), C-X-C motif chemokine 4 (CXCR4) and Hypoxia‐inducible glycolytic enzyme hexokinase‐2 (HK2) amongst many others. They work by affecting different mechanisms including influencing angiogenesis, treatment resistance, immune surveillance and the ability to metastasize all of which contribute to a more aggressive disease pattern. Tumour hypoxia has been correlated with poorer outcomes and worse prognosis in patients. The correlation between hypoxic microenvironments and poor prognosis has led to an interest in trying to therapeutically target this phenomenon. Various methods have been used to target hypoxic microenvironments. Hypoxia-activated prodrugs (HAPs) are drugs that are only activated within hypoxic environments and these agents have been subject to investigation in several clinical trials. Drugs that target downstream factors of hypoxic environments including HIF inhibitors, mammalian target of rapamycin (mTOR) inhibitors and vascular endothelial growth factor (anti-VEGF) therapies are also in development and being used in combination in clinical trials. Despite promising pre-clinical data, clinical trials of hypoxia targeting strategies have proven challenging. Further understanding of the effect of hypoxia and related molecular mechanisms in human rather than animal models is required to guide novel therapeutic strategies and future trial design. This review will discuss the currently available methods of hypoxia targeting and assessments that may be considered in planning future clinical trials. It will also outline key trials to date in both the solid and haemato-oncology treatment spheres and discuss the limitations that may have impacted on clinical success to date.